2014
DOI: 10.1016/j.det.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Photoaging

Abstract: This article discusses photoaging or premature skin aging from chronic ultraviolet exposure. This is an important cosmetic concern for many dermatologic patients. Clinical signs include rhytids, lentigines, mottled hyperpigmentation, loss of translucency, and decreased elasticity. These changes are more severe in individuals with fair skin and are further influenced by individual ethnicity and genetics. Photoaging may be prevented and treated with a variety of modalities, including topical retinoids, cosmeceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 48 publications
1
116
1
6
Order By: Relevance
“…In particular, ultraviolet radiation A is responsible for increased production of reactive oxygen species (ROS) which cause oxidative damage to cellular components such as DNA, lipids, proteins and mitochondria. 3 Clinical manifestation of skin photoaging includes rhytids, coarse texture, loss of translucency, pigmentation heterogeneities, elastosis and reduced turgor correlated with elastin and collagen degradation, decreased dermal and epidermal thickness owing to dermal cell and fibroblast apoptosis, precancerous lesions, and skin cancer. 3 The first line of defense against photoaging remains skin protection during sun exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, ultraviolet radiation A is responsible for increased production of reactive oxygen species (ROS) which cause oxidative damage to cellular components such as DNA, lipids, proteins and mitochondria. 3 Clinical manifestation of skin photoaging includes rhytids, coarse texture, loss of translucency, pigmentation heterogeneities, elastosis and reduced turgor correlated with elastin and collagen degradation, decreased dermal and epidermal thickness owing to dermal cell and fibroblast apoptosis, precancerous lesions, and skin cancer. 3 The first line of defense against photoaging remains skin protection during sun exposure.…”
Section: Introductionmentioning
confidence: 99%
“…3 Clinical manifestation of skin photoaging includes rhytids, coarse texture, loss of translucency, pigmentation heterogeneities, elastosis and reduced turgor correlated with elastin and collagen degradation, decreased dermal and epidermal thickness owing to dermal cell and fibroblast apoptosis, precancerous lesions, and skin cancer. 3 The first line of defense against photoaging remains skin protection during sun exposure. Symptomatic treatments include topical administration of retinoids, neuro-modulators, dermal fillers and the use of visible light devices.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The skin shows hypertrophic features with deep wrinkles, leathery appearance, dark/light pigmentation, sallowness, premalignant lesions, irregular dryness, and lentigines. [12] Other signs of aging include elastosis (a coarse, yellow, cobblestoned effect is on the skin) and actinic purpura (easy bruising corresponding to vascular wall fragility in dermis). [13] Figure 1 outlines the possible molecular mechanism of skin aging that takes place in the skin.…”
Section: Clinical Manifestation Of Photoagingmentioning
confidence: 99%
“…Main signs of photoaging include fine and deep wrinkles, dyspigmentation, loss of skin tone and elasticity [2,4]. Several studies have demonstrated that the skin can be stimulated to correct aging/ photoaging alterations by the intradermal injection of biological substances able to induce a revitalization of the dermis.…”
Section: Introductionmentioning
confidence: 99%
“…The changes of photo-damage are superimposed on the changes caused by chronological aging and are responsible for most of the age-associated features of skin appearance [2,3].…”
Section: Introductionmentioning
confidence: 99%